2009
DOI: 10.1007/978-1-4419-0901-5_7
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Recognition by Pentraxins

Abstract: Pentraxins are a family of evolutionarily conserved pattern-recognition proteins that are made up of five identical subunits. Based on the primary structure of the subunit, the pentraxins are divided into two groups: short pentraxins and long pentraxins. C-reactive protein (CRP) and serum amyloid P-component (SAP) are the two short pentraxins. The prototype protein of the long pentraxin group is pentraxin 3 (PTX3). CRP and SAP are produced primarily in the liver while PTX3 is produced in a variety of tissues d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
86
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(88 citation statements)
references
References 194 publications
1
86
1
Order By: Relevance
“…C‐reactive protein (CRP) is an acute‐phase protein of the family of the pentraxins and is widely used in clinical settings to monitor chronic and acute inflammatory conditions 1. The positive association between CRP levels and the risk of future coronary heart disease (CHD) has been studied extensively 2, 3.…”
Section: Introductionmentioning
confidence: 99%
“…C‐reactive protein (CRP) is an acute‐phase protein of the family of the pentraxins and is widely used in clinical settings to monitor chronic and acute inflammatory conditions 1. The positive association between CRP levels and the risk of future coronary heart disease (CHD) has been studied extensively 2, 3.…”
Section: Introductionmentioning
confidence: 99%
“…These evolutionarily highly conserved pattern recognition molecules (PRMs) are pivotal components of the innate immune system and are of great interest in relation to the pathogenesis of lupus. The affinity of CRP and other pentraxins for cell nuclear antigens, their ability to activate the classical complement pathway and their affinity for Fc-receptors is thought provoking in relation to deficient 'waste disposal' and ANA formation in SLE, where a CRP response is often low or absent despite raised interleukin 6 in disease flares [11][12][13]. Homozygous deficiency of C1q and C1r/C1s is associated with a very high risk to develop lupus (≥90%), whereas heterozygous genetic deficiency of C1 components appears not to be associated with decreased serum levels of C1q or an increased risk of developing SLE [14].…”
Section: Introductionmentioning
confidence: 99%
“…By using a multidisciplinary approach involving proteomics, binding assays, electron microscopy (EM), and in vivo studies, we demonstrated that rAAV-6 interacted specifically with C-reactive protein (CRP) in mice and galectin 3 binding protein (G3BP) in humans and dogs. Interestingly, CRP belongs to the short pentraxins, whose main functions are to recognize a variety of pathogenic agents (2), and G3BP contains a scavenger receptor cysteine-rich (SRCR) domain, which plays an important role in uptake and clearance of weakened components, such as modified host molecules and apoptotic cells (26,37). We found that in human serum human G3BP (hu-G3BP) was able to aggregate and precipitate rAAV-6.…”
mentioning
confidence: 99%